EFFECTS OF ADDED GROUND CORN GRAIN ON THE NUTRITIONAL VALUE AND PROTEIN DEGRADABILITY OF AN ENSILED MIXTURE OF COMMON VETCH AND OATS - Stojanović, Bojan (Journal of Agricultural Sciences (Belgrade), 2025)
Abstract: The aim of the study was to determine the effects of the addition of ground corn grain (CG) on the ensiling properties, nutritional value, and protein degradability of a forage mixture of common vetch and oats. Wilted and chopped vetch-oat forage was ensiled without treatment (VO) or after treatment with 50 or 100 g/kg (wet weight) of ground corn grain (VO+5% CG or VO+10% CG). The addition of CG significantly increased the dry matter content of silages (p<0.01), while crude protein (CP) content decreased by 4.7 and 9.3% in the VO+5% CG and VO+10% CG treatments, respectively. The use of CG in ensiled vetch-oat forage at 5 and 10% significantly increased (p<0.05) the nitrogen-free extract content by 4.8 and 11.7%, respectively. The addition of CG to ensiled forage resulted in higher values of lactic acid concentration (4.5 and 6.8%), especially when the proportion of milled grain was higher (p<0.05). Supplementation of CG to vetch-oat forage significantly lowered the pH of the silages (p<0.01). The use of ground CG in ensiled legume-cereal forage provided higher values for net energy (NE) concentration, which were significant (p<0.05) for NE for meat production. The ammonia-N concentration (protein fraction A1) was significantly lower (p<0.05) in the VO+5% CG and VO+10% CG treatments (15.8 and 21%, respectively). Soluble protein (CP fraction A2) was also significantly lower (p<0.01) in VO+5% CG and VO+10% CG silages (8.2 and 12.1%). Protein degradability was affected by supplementation of ensiled forage with CG (p<0.05 for Kp=5%/h and p<0.01 for Kp=8%/h), with the lowest degradability observed in VO+10% CG silages. It is suggested that supplementation of vetch-oat forage with ground corn grain, especially at a higher proportion (10 vs. 5% wet weight), has a favorable effect on fermentation parameters, the proportion of rumen undegradable protein (RUP) in CP, and nutritional value of the obtained silage.